2014
DOI: 10.1080/09168451.2014.885825
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a yam class IV chitinase produced by recombinant Pichia pastoris X-33

Abstract: A yam (Dioscorea opposita Thunb) class IV chitinase, whose genomic DNA was cloned by Mitsunaga et al. (2004), was produced by the recombinant Pichia pastoris X-33 in high yields such as 66 mg/L of culture medium. The chitinase was purified by column chromatography after Endoglycosidase H treatment and then characterized. It showed properties similar to the original chitinase E purified from the yam tuber reported by Arakane et al. (2000). This Pichia-produced chitinase also showed strong lytic activity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…In particular, the enzyme had its maximum activity at the highest acidity value assayed (pH 4). The stability of the maize chitinase is not surprising, because similar stabilities have also been reported for a similar class IV chitinase from yam ( Dioscorea opposita ) …”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In particular, the enzyme had its maximum activity at the highest acidity value assayed (pH 4). The stability of the maize chitinase is not surprising, because similar stabilities have also been reported for a similar class IV chitinase from yam ( Dioscorea opposita ) …”
Section: Discussionsupporting
confidence: 61%
“…In particular, the enzyme had its maximum activity at the highest acidity value assayed (pH 4). The stability of the maize chitinase is not surprising, because similar stabilities have also been reported for a similar class IV chitinase from yam (Dioscorea opposita) 20. From an allergological point of view, these results are particularly interesting, because they suggest that ChiA survives food-processing procedures and ingestion.…”
supporting
confidence: 68%
“…The native glycosylation of chitinases occurs in plants, insects and mammals, and in many cases is necessary for enzymatic activity [18][19][20]. Pichia pastoris is a popular expression system for the production of recombinant proteins, and chitinases expressed as recombinant enzymes in P. pastoris can be produced as either glycosylated or aglycosylated variants [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of chitinases have been characterized from monocotyledonous and dicotyledonous plant species . Some of these chitinases have been exploited as a biocontrol agent instead of chemical fungicides ,, or through transgenic plants overexpressing chitinases to enhance resistance against fungal pathogens. , Plant chitinase still has strong potential in controlling plant diseases. Given that each chitinase has its own properties that are important for specific functions, screening new chitinases with strong antifungal activity from other plants is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…However, extensive use of fungicides results in environmental and toxicological hazards . Therefore, utilizing the existing resistant and susceptible cultivars to screen resistance genes such as chitinase, studying the antifungal activity and characteristics of these chitinases, and developing natural antifungal resources to replace chemical fungicides , have become increasingly urgent tasks. Although chitinase is widely isolated in most plant species, research on sweet potato and its resistance to black rot disease has not been reported.…”
Section: Introductionmentioning
confidence: 99%